Community based multi-copied data delivery scheme for delay tolerant sensor network - Bin FU; Ren-fa LI; Xiong-ren XIAO; Ya-wei HUANG (Tongxin xuebao)
The characteristics of community structurehave effect on the data transmission procedure of delay tolerant mobile sensor network. Under the community network model,data delivery probabilities of multi-copied delivery were deduced. A community based multi-copy data delivery (CMDD)scheme was also proposed. By dynamically computing the average inter-meeting time between the communities and using the del ery probability formulations,the scheme can estimate the delivery probability when data are delivered through such community. Simulation results show that the pro-posed CMDD scheme achieves a relatively high data delivery ratio and a lower message delivery latency and transmis-sion overhead.